PENURUNAN KADAR KROM (Cr) DENGAN MENGGUNAKAN BIOMASA AMPAS TEBU SECARA BIO-ADSORBSI - Yasril, Yasril; Kasjono, Heru Subaris; Ganefati, Sri Puji (Jurnal Teknologi Lingkungan, 2009)
Chrome is a substance belong to high toxicity heavy metal group which can causeboth acute and chronic poisoning. One of the methods that can be used to reduceits concentration is biosorbtion with bagasse biomass. The objectives of the studywere to understand the chrome concentration before and after absorbed, as wellas to understand the amount of the most effective biomass.The study was an experimental with three treatments of which consisted of eightrepetitions. The sample was synthetic liquid waste and the treatment absorbentwas bagasse biomass which was processed as activated carbon of 10, 15, and 20grams weight. The chrome concentration were measured by using AAS method.The results showed that the chrome concentration before treated was 10,196mg/l, and the average of the reduction from the three absorbents weight were:0.174 mg/l, 0,099 mg/l, and 0,011 mg/l respectively.It can be concluded that there were reduction differences amongst the threetreatments, and 20 gr absorbent was the most effective one (99.88 % reduction).It is advised for further study to apply the bagasse for processing liquid waste fromindustrial activities.